Strategic Marketing Approaches for Pharmaceutical Industry in Penetrating Urban and Rural Markets in India – A Relative Analysis - Singh, Akash (Digital Repository of Theses - SSBM Geneva, 2025)
Background This research uses diverse methodologies to study pharmaceutical companies' strategic marketing in urban and rural India. It aims to understand current strategies, identify challenges, assess effectiveness through surveys, interviews, and data analysis, and customize marketing strategies for urban and rural consumers based on comprehensive secondary data analysis. Gaps in Current Studies Despite extensive research on Indian pharmaceutical marketing, gaps persist, particularly in differentiating rural and urban approaches: 1. Urban Bias: Existing studies often prioritize urban markets, ignoring crucial rural dynamics for tailored strategies. 2. Data Limitations: Some studies lack rural-urban data, limiting precise analysis and recommendations. 3. Consumer Behavior Oversight: Limited exploration of rural consumer behavior hampers strategy customization. 4. Digital Strategy Neglect: Studies inadequately address digital marketing’s role in rural and urban contexts, especially social media. 5. Cultural and Social Factors: Impact on marketing strategies remains underexplored despite significant influence on consumer behavior. 6. Affordability and Accessibility: Few studies addressing rural affordability and accessibility issues essential for targeted strategies. 7. Shortage of Longitudinal Studies: Lack of long-term studies tracking marketing strategy impacts over time, limits trend insights. Addressing these gaps will improve understanding of Indian pharmaceutical marketing, enhancing product accessibility, affordability, and consumer awareness in both markets. Methods 1. Data Collection: Mixed-methods approach including qualitative interviews and quantitative surveys. 2. Sampling: Includes healthcare providers, industry stakeholders, sales executives, managers, and diverse consumer demographics. 3. Data Analysis: Thematic analysis of interviews and statistical methods for quantitative data. Results The study aims to: 1. Identify differences in pharmaceutical marketing strategies between urban and rural markets. 2. Provide insights for policymakers, industry professionals, and healthcare providers to improve healthcare access for both. 3. Analyze factors influencing consumer behavior in both settings. 4. Assess challenges faced by companies in marketing their products, including impacts on availability and affordability. 5. Develop customized marketing strategies. 6. Investigate digital marketing and e-commerce in enhancing pharmaceutical product penetration. Discussion and Conclusion This research will provide insights into strategic marketing in India's pharmaceutical industry across urban and rural markets. It will help companies in understanding market dynamics and optimizing strategies for effective penetration through targeted approaches.